Pemanfaatan Limbah untuk Netralisasi Air Asam Tambang Menggunakan Granul Abu Terbang, Abu Dasar, dan Kotoran Kambing - Diah Permata Rinaldi; Irdika Mansur; Hamim (Postgraduate, University of Mataram, 2025)
Acid mine drainage (AMD) is one of the most serious environmental impacts of mining, characterized by low pH and high metal content. This study aimed to evaluate the neutralization efficiency of waste-based granules made from fly ash, bottom ash (FABA), and goat manure for AMD treatment under laboratory conditions. Two types of granules were produced: (i) 45% fly ash, 45% bottom ash, and 10% cement; and (ii) 45% fly ash, 30% bottom ash, 15% goat manure, and 10% cement. Each type was applied at different volumes (10%, 30%, and 50%) and positions (bottom and suspended) for 48 hours. Results showed that granule type, volume, and placement significantly influenced pH neutralization and metal removal. The best performance was achieved by the suspended granule without manure at 50%, raising AMD pH from 2.45 to 9.17 within 3 hours, with 88.7% Fe and 66.5% Mn removal. XRD and Micro-XRF analyses confirmed that neutralization occurred through dissolution of Ca-based minerals and formation of calcite and gypsum. The study demonstrates that FABA granules offer a low-cost, sustainable option for AMD treatment and can serve as a contextual learning model in environmental and chemistry education, linking waste utilization with real-world applications of acid-base reactions and environmental sustainability.